Interactive Multimedia Based on a Contextual Approach to Material Changes in the form of Objects - Cindy Pradnyawati; Ni Wayan Rati (Universitas Pendidikan Ganesha, 2023)
This development research was motivated by the need for more student V learning outcomes in science due to less creative and innovative learning media. This study aims to develop a design and test interactive multimedia's validity, practicality, and effectiveness based on a contextual approach. This type of research is development. The research model used is ADDIE. The object of research is interactive multimedia based on a contextual approach with student subjects. Data collection methods used are interviews, observation, questionnaires, and tests. The data analysis method or technique used is descriptive qualitative analysis, quantitative, and inferential statistics. The results show that the developed interactive multimedia is valid based on expert tests on material, design, media, individual trials, and small group trials. Multimedia is classified as practical based on student response tests and observation of learning implementation. The t-test results showed differences in learning outcomes in the science content material for changes in the shape of objects for fifth-grade elementary school students. Based on this, interactive multimedia based on a contextual approach is feasible and effective to be implemented in class V SD.